City Image Model in Creating Tourist Engagement - Setiawan, Rahyuniati; Garliani, Gita; Berliani, Syifa; Yuliawati, Yupi (KnE Social Sciences, 2023)
The problem in this study is the decline in tourist visits to hot spring natural tourist destinations in Indonesia during the Covid-19 pandemic. City image and nostalgic emotion play an essential role in influencing tourist engagement through memorable tourism experiences as mediation for visiting tourist destinations. This study aims to determine the effect of city image and nostalgic emotion on tourist engagement within memorable tourism experiences as a mediation. The research subjects were tourists in natural hot spring tourist destinations in West Java Province. The method used in this research was the explanatory survey. Respondents in this study were visitors to hot spring natural tourist destinations in Indonesia accidentally, totaling 400 people. The sampling technique used in this research was proportional random sampling. Keywords: city images, nostalgic emotions, memorable tourism experiences, tourist engagement